Appearance Teasing and Mental Health: Gender Differences and Mediation Effects of Appearance-Based Rejection Sensitivity and Dysmorphic Concerns - Schmidt, Jennifer; Martin, Alexandra (Frontiers in Psychology, 2019)
Appearance teasing is a common phenomenon in social interactions, especially in adolescence. Several studies have shown its negative impact on mental health as well as on body image. While these findings prove stable in various contexts, less evidence is available for possible gender differences in these relationships. In particular, the role of two important body image variables – appearance-based rejection sensitivity (ARS) and dysmorphic concerns – and their contribution to mental health impairments has not been assessed in gender-specific process models. In a cross-sectional survey-study (N = 501; 407 f, 94 m), we retrospectively assessed early appearance teasing experiences, as well as current ARS, dysmorphic concerns, depression, anxiety, and self-esteem. We analyzed gender differences in these variables and their interrelations. We then examined the mediating role of ARS and dysmorphic concerns in explaining mental health variables in adulthood due to early appearance teasing in gender-specific serial-mediation models. The results show high ratios of early teasing experiences, but no significant gender difference regarding the frequency of early appearance teasing. While teasing experiences were significantly related to body image variables in adulthood in both genders (rs > .32; ps < .010), we observed significant relations with mental health outcomes in women (rs > .30; ps <.001) but not in men (rs <.20; ps > .250). Serial mediation models show that ARS and dysmorphic concerns mediate the effects of appearance teasing on mental health in all outcomes in women (R² > .17), but not in men (R² < .03). Findings remained stable when controlling for Body-Mass-Index, age, and relationship-status. The findings show similar frequencies of appearance teasing and associated negative effects on body image in men and women. Specifically, in women, the effects of teasing on mental health were stronger and mediated by ARS and dysmorphic concerns. Overall, the results point to the relevance of ARS for etiological models of body image disorders and female mental health. However, men did not show the same relationships of teasing and mental health. Differential resilience factors regarding the negative effects of early appearance teasing could be an important target for future research.